Draft Five Year Plan 1978-83 Development of Languages Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Located in the heart of India, Madhya Pradesh is the largest Hindi speaking state of the country in which numbers of dialects are spoken. These dialects have their own cultural heritage and literature both written and spoken. If proper study is made of these dialects and expressions and terms prevalent in these dialects are compiled and preserved, it would definitely enrich our official language. Besides, this attempt would bring the public in general closer to the official language and also make them feel that the official language rightly represents their cultural heritage.
Government of Madhya Pradesh, Planning, Economics and Statistics Department